Everyday SEL in the virtual classroom integrating social emotional learning and mindfulness into your remote and hybrid settings - Tantillo Philibert, Carla; Slade, Allison (New York, NY Routledge, Taylor & Francis Group, 2022)
"This essential new resource from wellness experts Carla Tantillo Philibert and Allison Slade will help you build students' self-awareness and self-regulation, teacher trust and school connectedness, social awareness, voice, and agency in remote or hybrid settings. Appropriate for teachers of all grade levels, as well as for instructional leaders and parents, the book emphasizes the educator's own self-care and emotional intelligence, so you can become more aware of how the environment is affecting you before you can help others. It also offers ideas for planning collaboratively with colleagues and engaging families in the virtual environment"--
Introduction -- Becoming emotionally intelligent in a virtual teaching environment -- Creating the climate and conditions for a socio-emotionally healthy virtual classroom -- Self-awareness and self-regulation -- School connectedness and teacher trust -- Social awareness : activities to promote social interaction virtually -- Student voice and agency -- Virtual SEL for collaborative planning with colleagues -- Engaging families in SEL in the virtual environment -- Conclusion.
Includes bibliographical references.
Keywords: Affective education; Mindfulness (Psychology); Reflective teaching; Web-based instruction -- Psychological aspects